1977
DOI: 10.1104/pp.59.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Area Partitioning as an Important Factor in Growth

Abstract: Despite continuing efforts to correlate unit area rates of photosynthesis of crop varieties with growth rates, there has been little or no success. It is reasonable to assume that partitioning of photosynthate into new leaf area is an important component of growth. Accordingly, an expression was developed to measure leaf area partitioning. Using growth analysis techniques, relative growth rates were compared to net assimilation rates, partitioning of daily weight gain into new leaf area, and partitioning of da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
87
1
1

Year Published

1987
1987
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(97 citation statements)
references
References 24 publications
8
87
1
1
Order By: Relevance
“…3). The data for S. vlulgaris is consistent with data obtained with many other species in finding that ULR, which is primarily determined by unit area photosynthetic rate, is poorly correlated with biomass production (21).…”
Section: Growth Analysissupporting
confidence: 79%
See 1 more Smart Citation
“…3). The data for S. vlulgaris is consistent with data obtained with many other species in finding that ULR, which is primarily determined by unit area photosynthetic rate, is poorly correlated with biomass production (21).…”
Section: Growth Analysissupporting
confidence: 79%
“…Furthermore, our data indicate that leaf size and cumulative LAD have a greater impact on biomass accumulation than does photosynthetic rate. Other studies have also concluded that the combination of photosynthetic rates and development of leaf area are major determinants of growth and competitive ability (21). These results suggest that the yield of triazine resistant crops may be improved by increasing leaf area and cumulative LAD to partially compensate for the reduced productivity of triazineresistant chloroplasts.…”
Section: Growth Analysismentioning
confidence: 58%
“…Similarly, an organ weight partitioning coefficient is the ratio of the absolute growth rate of the organ in question (for example, leaves) divided by the absolute whole plant growth rate at any given time during the harvest period. The NAR and partitioning coefficients were calculated at the midpoint ofthe harvest period, because the confidence in the value of the coefficients is greatest at this point (21 Leaf weight per unit area was independent of Na in A. retroflexus (Fig. 2).…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, the higher PNUE of C4 species may allow them to allocate a greater fraction of available N to new leaf, root, or stem production. Increasing N availability increases the leafexpansion rate (8,14,26,27), which is well correlated with growth rate (21). Moreover, reductions in yield following N deficiency are often due more to reduced leaf expansion rates than to a decline in photosynthesis rate per unit area (8,10,27).…”
mentioning
confidence: 98%
“…(12) where ΔL gx max is the maximum rate of change in expanding leaf area for a given change in x g (cm 2 plant −1 unit x g -1 ), x g is the cumulative f (T ) since emergence, where f (T ) is a temperature response function related to phenology based on observed data (Equation (11)) with minimum (T min ), optimum (T opt ), and maximum (T max ) temperatures of 0, 33, and 50 °C, respectively. The temperature response function (Equation (11)) for leaf expansion (f (T g ), Figure 1) takes the same form as for phenology but with different T min , T opt , and T max , 4, 26, and 40 °C, respectively (Potter and Jones, 1977;Tardieu et al, 2005;Wright et al, 1999). The water deficit response function for leaf expansion ( f (TR a /TR p ) is given by Equation (12).…”
Section: Model Developmentmentioning
confidence: 99%